Human T‐lymphotropic virus lookback in NHS Blood and Transplant (England) reveals the efficacy of leukoreduction. Issue 10 (5th February 2013) - Hewitt, Patricia E.; Davison, Katy; Howell, David R.; Taylor, Graham P.
<x xml:space="preserve">Abstract</x> Background Leukoreduction of blood components was introduced in the United Kingdom during 1998. Human T‐lymphotropic virus (HTLV) screening of blood donations was introduced in 2002. NHS Blood and Transplant conducted an HTLV lookback on blood components issued before 2002. A proportion of included components were nonleukoreduced, although the majority were subject to white blood cell reduction measures. Study Design and Methods A standard lookback was conducted on untested cellular blood components from donors later confirmed to be HTLV positive, for the 4 to 5 years before 2002, and on the last tested negative donation from donors who had seroconverted. Results A total of 437 red blood cell and platelet components were included and an outcome was reported for 84% of these. Just over half of identified recipients were dead at the time of lookback; blood samples for testing were obtained from 77% of identified living recipients. HTLV infection was confirmed in seven recipients, but one was discounted as not transfusion transmitted. Conclusion Although numbers are small, our results provide evidence of the efficacy of leukoreduction in reducing the likelihood of HTLV transmission through transfusion of cellular blood components. The HTLV‐positive rate in recipients of leukoreduced components was 3.7%, a reduction of 93% compared with nonleukoreduced components. Importantly, the one infected recipient of a leukoreduced component had existing risk factors for HTLV infection. HTLV lookback was much less efficient in identifying infected recipients than was hepatitis virus C lookback.